Incidence and Risk of Concussions in Youth Athletes: Comparisons of Age, Sex, Concussion History, Sport, and Football Position - Tsushima, William T (Arch Clin Neuropsychol, 2018)
OBJECTIVE: This study was designed to determine concussion incidence, risk, and relative risk among middle and high school athletes participating in various sports. METHOD: Data were retrospectively obtained from 10,334 athletes of 12 different sports in Hawaii. In addition to determining the overall concussion incidence, comparisons of incidence, risk, and relative risk were made according to age, sex, concussion history, sport, and football position. RESULTS: The overall incidence of concussion among youth athletes was 1,250 (12.1%). The relative risk for a concussion was almost two times greater in 18-year olds than in 13-year-old athletes. In comparable sports, girls had a 1.5 times higher concussion risk than boys. Athletes with a prior concussion had 3–5 times greater risk to sustain a concussion than those with no history of a concussion. Among varied sports, wrestling and martial arts had the highest relative risk of a concussion, followed by cheerleading, football, and track and field. No differences in concussion risks were found among the football players in different positions. CONCLUSIONS: Older youths, females, those with a history of concussion, and those participating in high contact sports were found to have higher risks of sustaining a concussion. The findings increase awareness of concussion patterns in young athletes and raise concerns regarding protective strategies and concussion management in youth sports.